2010
DOI: 10.1007/s00421-010-1596-2
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow differentially affects near-infrared spectroscopy-derived measures of muscle oxygen saturation and blood volume at rest and during dynamic leg exercise

Abstract: The impact of skin blood flow changes on near-infrared spectroscopy (NIRS)-derived measures of muscle oxygen saturation (SmO(2)) and blood volume has not been fully established. We measured SmO(2) and total hemoglobin concentration ([tHb]) responses of the right vastus lateralis during rest and dynamic knee extension exercise in ten young, healthy males. The protocol was repeated four times: twice without thigh heating for reliability, and twice with different grades of thigh heating for assessing the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 25 publications
(42 reference statements)
3
70
1
Order By: Relevance
“…A recent study [42] provided reassurance that changes in SmO 2 during exercise predominantly reflect muscle oxygenation, even during conditions where skin and muscle blood flow were elevated concomitantly (e.g. during prolonged, dynamic exercise).…”
Section: Open Questionsmentioning
confidence: 99%
“…A recent study [42] provided reassurance that changes in SmO 2 during exercise predominantly reflect muscle oxygenation, even during conditions where skin and muscle blood flow were elevated concomitantly (e.g. during prolonged, dynamic exercise).…”
Section: Open Questionsmentioning
confidence: 99%
“…Indeed, StO 2 was recorded at a maximum depth of 15 mm including cutaneous and muscular vessels. Moreover, previous studies suggest that compression sleeves may affect cutaneous StO 2 through temperature changes (13,27) and pressure-induced skin vasodilation (26).…”
Section: Changes In Sto2 At Restmentioning
confidence: 99%
“…These results are in accordance with previous research, which reported that StO2 increased with calf compression sleeves before and after running or cycling exercises (13,19). The higher StO 2 was attributed to the increased muscle flow rate (9, 10) and changes in skin blood flow with calf compression sleeves (26,27). Indeed, wearing compression on the lower limbs is known to increase venous return (2), causing venous pressure to decrease (1).…”
Section: Changes In Sto2 At Restmentioning
confidence: 99%
See 1 more Smart Citation
“…NIRS gain or laser power must then be modulated to fit with the skin properties of a given subject; which can be performed automatically by the NIRS hardware before starting the data acquisition. Skin blood flow is one of the main confounding factors as the haemoglobin molecules present in the capillary beds located in the skin are the first (and last) exposed to NIRS light (Tew et al, 2010). In exercising subjects, blood flow is increasing in proportion to the intensity of exercise, for well-known thermoregulation reasons.…”
Section: Confounding Factorsmentioning
confidence: 99%